Analisis Semiotik Makna Perjuangan Seorang Ibu Dalam Lagu Dawai (Air Mata Di Ujung Sajadah) - Muhamad Topan Slamet Nurdin (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
Humans need information to support the process of interaction with other humans. Songs are a medium for artistic and cultural expression that depict human life, religion and the personality of a nation. Family is the place where children are raised and educated. mothers gain other roles as they become a single parent because of death of the spouse or divorce. The mother's role increases because she also acts as a father figure who is not in the family. Dawai Song (Tears at the End of the Sajadah) contains the figure of the struggle of a mother who was separated from her 7 year old child by her grandmother. Based on the explanation above, the aim of the problem is to find out the meaning of a mother's struggle and the meaning of denotation, connotation and myth in the song Dawai (Air Mata Di Ujung Sajadah)? This research methodology uses a qualitative approach with descriptive analysis methods. This analysis uses semiotic theory which refers to Roland Barthes' model, which focuses on the meaning of denotation, connotation and myth.